Золь-гель синтез і оптичні властивості кварцових стекол, легованих перехідними металами - Borysenko, M. V.; Frolova, O. K.; Borysenko, L. I.; Sulym, I. Ya.; Galaburda, M. V.; Bogatyrov, V. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2013)
A new variant of the sol-gel synthesis of the quartz glass activated with transition metal oxide nanoparticles have been developed. The resulting doped glass has a high optical homogeneity, contains ~ 0.3 wt. % OH groups and different high refractive index compared to pure silica glass.